Perceptions Differences in Smile Attractiveness Between Dental Students’ and Lay Persons’ - Joko Kusnoto; Sarah Tiara Haryanto (Indonesian Dental Association, 2021)
Introduction: Orthodontic treatment is performed to improve dental alignment, function, oral health, dentofacial stability and to achieve better facial esthetics. People tend to seek orthodontic treatments for a more esthetically attractive smile. Several parameters are used to measure the attractiveness of smiles, including the smile arc, smile line, buccal corridor or smile type, and smile symmetry. Perceptions of the various aspects of smile attractiveness may differ among patients and dentists, so dentists must understand patients’ perceptions of the aspects of smile attractiveness in order to provide satisfactory care. Objective: To determine if there are differences in the perceptions of dental students and lay persons regarding the aspects of smile attractiveness. Methods: This is an analytical observational study with a cross-sectional research design. This study was conducted by distributing questionnaires containing 11 photographs of manipulated smiles to 50 students currently training to become dental professionals and 50 lay persons. The data were analyzed using an independent t-test. Results: A significant difference in perception (p < 0.05) found in the smile line parameter. However, there were no significant differences in perception (p > 0.05) with regard to smile arc, smile type, or smile symmetry parameters. Conclusions: Dental students and lay persons have different perceptions regarding smile line but share the same perception of smile arc, smile types, and smile symmetry.